512 TMS Seeded DTI Tractography Provides Superior Identification of Eloquent Cortex Compared to Anatomic Seeded Tractography. (1st March 2022) - Muir, Matthew; Prinsloo, Sarah; Traylor, Jeffrey I.; Bastos, Dhiego; Prabhu, Sujit S.
Abstract : INTRODUCTION: Previous studies have shown the feasability of seeding DTI tractography using transcranial magnetic stimulation (TMS) points for the cortical region of interest (ROI). Previous work from our group has shown that resection of TMS points with connecting white matter tracts identified by TMS tractography leads to permanent neurological deficits. METHODS: We selected a cohort of 42 patients with perirolandic gliomas who underwent preoperative TMS mapping with subsequent resection. The primary outcome collected from the chart was new or worsened motor deficit present at 3 month follow up. We overlayed the postoperative resection cavity onto the preoperative MRI containing the tractography data, seeded either by TMS points or the precentral gyrus. We used a confusion matrix to model the predictive value of permanent deficits for each tractography scheme. Positive predictive value denotes the likelihood that a patient with the corresponding tract resected develops a permanent deficit, while negative predictive value denotes the likelihood that a patient with the corresponding tract preserved does not develop a permanent deficit. RESULTS: 22/42 patients showed TMS positive points significantly displaced from the precentral gyrus. With respect to prediction of permanent deficit upon resection of relevant tracts versus preservation of relevant tracts, TMS seeded tractography showed a positive predictive value (PPV) of 87% and negative predictive value (NPV) of 97%. Anatomic tractography showed a positive predictive value (PPV) of 50% and negative predictive value (NPV) of 91%. CONCLUSION: Over half of the patients in our cohort exhibited tumor induced plasticity measured by TMS. TMS seeded tractography provided significantly higher positive and negative predictive value for identifying true non-resectable, eloquent cortex compared to anatomic seeded tractography.